Presence of drugs and hormones in water: a scientometric analysis (Research, Society and Development, 2018)
Among the forms of water degradation, there is an increased interest in certain potentially toxic substances, such as natural and synthetic hormones, personal hygiene products, drugs and pesticides, known as micropollutants. In this context, this research aimed to evaluate the spatiotemporal evolution of the scientific works that address the presence of drugs and hormones in sewage treatment plant effluents and water supply sources. For this, 317 articles, selected in the Web of Science database, published between the years of 1998 and 2016, have been used as a sample, using the random simple probabilistic sampling technique by sortition. There was an increase in the number of publications from the year 2000, which, however, did not continue to increase until the year 2016. Among the reviewed journals, those in the environmental area had a greater number of articles related to the emerging micropollutants, United States of America (USA) corresponds to the country with the largest number of publications (28%). The most frequently mentioned pharmacological substances were carbamazepine and paracetamol or acetaminophen, while those with hormonal effects were bisphenol-A and nonylphenol. The technologies that stood out in the removal of micropollutants correspond to the oxidation, treatment by membranes and ultraviolet. It should be emphasized that in order to monitor the presence of drugs and hormones in water resources, it is necessary to formulate and implement laws to establish parameters for these pollutants, as well as to encourage research to identify their effects on aquatic ecosystems and health human.